1994
DOI: 10.1007/bf02310936
|View full text |Cite
|
Sign up to set email alerts
|

An evolutionary approach to associative memory in recurrent neural networks

Abstract: Abstract. In this paper, we investigate the associative memory in recurrent neural networks, based on the model of evolving neural networks proposed by Nolfi, Miglino and Parisi.Experimentaily developed network has highly asymmetric synaptic weights and dilute connections, quite different from those of the Hopfield model.Some results on the effect of learning efficiency on the evolution are also presented. IntroductionAs a model of associative memory in terms of the recurrent-type artificial neural networks, H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…There are many papers reported using EC to replace the back-propagation learning algorithm in ANN in the past several years ( [1], [2], [7], [8], [9], [10], [12], [14], [18], [19], [20], [22], [26], [27], [28]). They showed that EC is a promising method for training ANN.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…There are many papers reported using EC to replace the back-propagation learning algorithm in ANN in the past several years ( [1], [2], [7], [8], [9], [10], [12], [14], [18], [19], [20], [22], [26], [27], [28]). They showed that EC is a promising method for training ANN.…”
Section: Experimental Studiesmentioning
confidence: 99%